The Pinter ethic : the erotic aesthetic - Prentice, Penelope (Garland, 2000)
The only comprehensive guide to the plays of one of the world's greatest yet most puzzling contemporary dramatists.
Originally published: 1994.
Keywords: Pinter, Harold, -- 1930-2008 -- Ethics.; Pinter, Harold, -- 1930-2008 -- Aesthetics.; Pinter, Harold, -- 1930-2008; Didactic drama, English -- History and criticism.; Ethics in literature.; Love in literature.; Sex in literature.; Morale dans la littérature.; Amour dans la littérature.; Sexualité dans la littérature.; DRAMA -- English, Irish, Scottish, Welsh.; Aesthetics; Didactic drama, English; Ethics; Ethics in literature; Love in literature; Sex in literature; Electronic books.; Criticism, interpretation, etc.